Senegal : Request for Disbursement Under the Rapid Credit Facility and Purchase Under the Rapid Financing Instrument-Press Release; Staff Report; and Statement by the Executive Director for Senegal. (International Monetary Fund, 2020)
The COVID-19 pandemic has weakened the macroeconomic outlook for Senegal's economy. Containment measures to avoid the propagation of the virus, lower external demand, reduced remittances, and the sudden stop of travel and tourism are having a significant impact on growth and generating an urgent budgetary and balance-of-payments (BOP) needs. The authorities have taken strong actions to address the pandemic by declaring a state of emergency, closing schools, suspending flights, banning public gatherings, and imposing a curfew. They are implementing a comprehensive plan to upgrade the health system and contain the economic impact, including by setting up a national solidarity fund and providing targeted support to vulnerable households and firms.